2017
DOI: 10.1007/s40037-017-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the connection between the classroom and the clinical workplace: A systematic review

Abstract: IntroductionAlthough medical students are increasingly exposed to clinical experiences as part of their training, these often occur parallel with, rather than connected to, their classroom-based learning experiences. Additionally, students seem to struggle with spontaneously making the connection between these spheres of their training themselves. Therefore, this systematic review synthesized the existing evidence about educational interventions that aim to enhance the connection between learning in the classr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…The learning opportunities provided within the scope of Oral Medicine practice need to be inclusive and take account of different learning styles that allow individuals to reach common endpoints via different routes. The challenges of linking teaching outside the clinic to that involving clinical care are recognised across health care . Irrespective of the approaches used, all need to deliver the common goal of supporting development of adequate clinical‐reasoning and decision‐making skills at the point of becoming a registered dentist.…”
Section: Oral Medicine For Undergraduate Dental Students ‐A Curriculummentioning
confidence: 99%
“…The learning opportunities provided within the scope of Oral Medicine practice need to be inclusive and take account of different learning styles that allow individuals to reach common endpoints via different routes. The challenges of linking teaching outside the clinic to that involving clinical care are recognised across health care . Irrespective of the approaches used, all need to deliver the common goal of supporting development of adequate clinical‐reasoning and decision‐making skills at the point of becoming a registered dentist.…”
Section: Oral Medicine For Undergraduate Dental Students ‐A Curriculummentioning
confidence: 99%
“…This article contains practical suggestions for clinical teachers to help make the connection between the classroom and the workplace more explicit to students. It is based on recent literature reviews, qualitative research, and the authors’ experiences in supporting students and clinical teachers in the context of postgraduate general practice training. Although these recommendations arose from a context in which there is mainly one‐to‐one coaching in the workplace, these recommendations may be helpful in any medical context.…”
Section: Application Of Research To Practicementioning
confidence: 99%
“…case‐based learning and simulation education) and in the workplace (e.g. feedback sessions). These initiatives seem to have beneficial outcomes for students and often involve support from clinical teachers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Some studies have shown the effectiveness of educational methods on students' learning. [5][6][7] One educational method often recommended is small group discussion learning or small group learning for students. Since many methods of learning have been introduced in education, choosing a suitable and effective method is necessary.…”
Section: Introductionmentioning
confidence: 99%